Scientific literature on carbon dioxide removal revealed as much larger through AI-enhanced systematic mapping - Sarah Lück; Max Callaghan; Malgorzata Borchers; Annette Cowie; Sabine Fuss; Matthew Gidden; Jens Hartmann; Claudia Kammann; David P. Keller; Florian Kraxner; William F. Lamb; Niall Mac Dowell; et al. (Nature Communications)
Abstract Carbon dioxide removal plays an important role in any strategy to limit global warming to well below 2 °C. Keeping abreast with the scientific evidence using rigorous evidence synthesis methods is an important prerequisite for sustainably scaling these methods. Here, we use artificial intelligence to provide a comprehensive systematic map of carbon dioxide removal research. We find a total of 28,976 studies on carbon dioxide removal—3–4 times more than previously suggested. Growth in research is faster than for the field of climate change research as a whole, but very concentrated in specific areas—such as biochar, certain research methods like lab and field experiments, and particular regions like China. Patterns of carbon dioxide removal research contrast with trends in patenting and deployment, highlighting the differing development stages of these technologies. As carbon dioxide removal gains importance for the Paris climate goals, our systematic map can support rigorous evidence synthesis for the IPCC and other assessments.